Hybrid Artificial Intelligent Systems 6th International Conference, HAIS 2011, Wroclaw, Poland, May 23-25, 2011, Proceedings, Part I - Corchado, Emilio; Kurzynski, Marek; Wozniak, Michal (Lecture Notes in Artificial Intelligence, 2011)
The two LNAI volumes 6678 and 6679 constitute the proceedings of the 6th International Conference on Hybrid Artificial Intelligent Systems, HAIS 2011, held in Wroclaw, Poland, in May 2011. The 114 papers published in these proceedings were carefully reviewed and selected from 241 submissions. They are organized in topical sessions on hybrid intelligence systems on logistics and intelligent optimization; metaheuristics for combinatorial optimization and modelling complex systems; hybrid systems for context-based information fusion; methods of classifier fusion; intelligent systems for data mining and applications; systems, man, and cybernetics; hybrid artificial intelligence systems in management of production systems; habrid artificial intelligent systems for medical applications; and hybrid intelligent approaches in cooperative multi-robot systems.